Study using endoscopic procedures for removal of foreign bodies from aero-digestive tract conducted in Jahurul Islam Medical College Hospital, Bangladesh - Islam, MS; Gafur, MA; Deb, PK; Bardhan, A; Noor, L (Mediscope, 2016)
Foreign bodies (FB) in the aero-digestive tract continue to be a common problem that contributes significantly to high morbidity and mortality worldwide. This study was conducted to describe our own experience with endoscopic procedures for removal of FB in the aero-digestive tract, in our local setting and compare with what is described in literature. This was a prospective descriptive study, which was conducted at Jahurul Islam Medical College Hospital between January, 2011 and January, 2014. Data were collected using a structured questionnaire and analyzed using SPSS computer software version 15. A total of 72 patients were studied. Males outnumbered females by a ratio of 1.4:1. Patients aged 2 years and below were the majority (75.9%). The commonest type of FB in airways was peanuts and coins. The trachea (52.2%) was the most common site of lodgment of FB in the airways, whereas cricopharyngeal sphincter (68.5%) was the commonest site in the esophagus. Rigid endoscopy with forceps removal under general anesthesia was the main treatment modality performed in 87.8% of patients. The FB were successfully removed without complications in 90.8% of cases. Complication rate was 7.1% and bronchopneumonia was the most common complication accounting for 42.8% of cases. The mean duration of hospital stay was 3 days and mortality rate was 4.1%. Aero-digestive tract FB continue to be a significant cause of childhood morbidity and mortality in our setting. Rigid endoscopic procedures under general anesthesia are the main treatment modalities performed. Prevention is highly recommended whereby parents should be educated to keep a close eye on their children and keep objects that can be FB away from childrens reach. Mediscope Vol. 3, No. 1: January 2016, Pages 22-27